Hubungan antara Financial Distress dan Model Prediksi Kesehatan Keuangan: Studi pada Perusahaan Manufaktur Publik yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2019-2024 - Nenie, Nenie; Sari, Pristin Prima; Maulida, Alfiatul (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study analyzes the influence of financial ratios, including profitability, liquidity, and activity ratios, on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period, specifically in the context of the Covid-19 pandemic. Twenty manufacturing companies on the IDX were selected as samples using a purposive sampling method, and quantitative data were analyzed using multiple linear regression. The Altman Z-Score method was used to measure financial distress. These findings specifically show that the Covid-19 pandemic has had a significant impact on the decline in companies' financial health, primarily through decreased profitability and asset utilization efficiency. Based on these results, companies are advised to focus more on these two issues to reduce the risk of financial distress, especially when facing an unexpected economic crisis such as the pandemic.